Assessing Adolescents’ Perception of Sources and Barriers to Sexual Reproductive Health Information and Services in Metropolitan Lagos, Nigeria - Lawal, Moshood Babatunde; Obani, Lateefat Adeola; Saka, Latifat Apeke (NIU Journal of Humanities; Vol 10 No 4 (2025): NIU Journal of Humanities, Vol. 10 No. 4, December 2025, 2025)
This study examines adolescents' perceptions of sexual and reproductive health (SRH) information and services in Metropolitan Lagos, Nigeria, addressing gaps in access influenced by cultural, educational, and systemic barriers. A survey of 228 adolescents (83.8% female; 82% aged 18–19 years) revealed significant challenges: 38.2% reported no maternal communication on SRH, and over 50% cited insufficient school-based SRH education. Privacy concerns, fear of judgment, financial constraints, and healthcare provider stigma emerged as critical barriers, with 54.8% highlighting confidentiality fears. Gender analysis showed no significant differences in perceptions of SRH sources or barriers, though females demonstrated greater awareness of available services. Post-secondary educated adolescents perceived higher systemic barriers than their secondary-educated peers. The study underscores the impact of cultural taboos, inadequate parental engagement, and poorly implemented SRH curricula. Recommendations include integrating comprehensive SRH education into school programs, establishing youth-friendly health services prioritizing confidentiality and affordability, leveraging media for awareness campaigns, and enhancing parental communication. Community outreach and technology-based interventions are proposed to bridge gaps for out-of-school adolescents. Addressing these barriers is vital to improving SRH outcomes, reducing unintended pregnancies, and empowering adolescents to make informed health decisions, necessitating collaborative efforts among policymakers, educators, healthcare providers, and families. Keywords: Adolescents, Perception, Barriers, Sexual reproductive health, Nigeria